Leptomeningeal Metastasis from Non-small Cell Lung Cancer: Survival and the Impact of Whole Brain Radiotherapy - Morris, Patrick G.; Reiner, Anne S.; Szenberg, Olga Rosenvald; Clarke, Jennifer L.; Panageas, Katherine S.; Perez, Hector R.; Kris, Mark G.; Chan, Timothy A.; DeAngelis, Lisa M.; Omuro, Antonio M. (Journal of thoracic oncology, 2012)
Leptomeningeal metastasis (LM), or leptomeningeal carcinomatosis, is a devastating complication of non-small cell lung cancer (NSCLC), and the optimal therapeutic approach remains challenging. A retrospective review was carried out to assess the impact of whole brain radiotherapy (WBRT), intrathecal therapy (IT), and epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) on outcomes. Patients with newly diagnosed LM from NSCLC from January 2002 to December 2009 were identified through institutional databases and medical records reviewed. Survival was assessed by Kaplan-Meier and landmark analyses by administered treatment to minimize selection bias. We identified 125 patients (45 men, 80 women) with LM from NSCLC, median age 59 years (range, 28–87 years). Almost all (123 [98%]) patients have died and median overall survival was 3.0 months (95% confidence interval, 2.0–4.0). No differences in survival were seen between patients who were treated with WBRT (n =46) and those who were not (n =59, p =0.84) in a landmark analysis. In the seven patients selected to receive IT chemotherapy, median survival was 18 months (range, 5–33 months) and appeared superior to those not selected for this treatment (p =0.001) in a landmark analysis. The median survival of the nine patients with known EGFR mutations (all of whom received TKIs at some point) was 14 months (range, 1–28 months). This retrospective study, the largest published series, demonstrates the poor survival of LM from NSCLC. In this study, survival was not improved by WBRT. The survival of patients selected for IT chemotherapy and those with EGFR mutations treated with TKIs highlights the importance of developing novel agents.